Exploring Ethical Dilemma in Big Data Analytics: A Literature Review - Leung, Kelvin Tak Yiu; Dembicz, Antos; Stevenson, Anne (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Big data analytics has remarkably transformed every sector of the world, including the Emergency Service sector, health sector, science, and space, as well as the business sector, in the way they manage and run their activities every day. Big data analytics has made it possible and easier for all of these sectors to predict future outcomes, make more adequate critical decisions, and take more effective actions respectively. It now gives businesses the power to obtain, access, and leverage customers’ data, and even control their behaviors. Many sectors are leveraging big data in that respect, especially businesses. They are incorporating big data analytical tools to obtain their users’ data and access their personal information, such as their interests, behavioral pattern, ideas, security details, personal interactions, etc, which they store and leverage for their benefits. This information is obtained and accessed usually without the conscious knowledge and approval of their consumers. This is the major factor that has raised ethical concerns among several leaders and experts about the extent of the personal information that can be accessed, as well as the safety and wellbeing of the common people who are unaware that their personal information is being obtained, accessed, and used. Another concern is about the freedom of individuals. With the innovation and implementation of big data analytics, many of the businesses can technically control their users; what they want, need, and do, and thus, depriving them of the freedom to make decisions on their own. There is also another concern concerning the safety of the intellectual property of individuals and corporations. Big data analytics can lead to intellectual property infringement and theft, thereby denying people and bodies the right to their ideas and innovations. While on one hand big data analytics yield great promises, on the other hand, it raises critical ethical (security and privacy) issues, which if left unaddressed may become significant barriers to the fulfillment of expected opportunities and long-term success of big data. In this paper, we discuss the ethical dilemmas in big data analytics.